Observational analysis of late-time acceleration in f (Q, Lm ) gravity - Myrzakulov, Kairat; Koussour, M.; Donmez, O.; Cilli, A.; Gudekli, E.; Rayimbaev, J. (ELSEVIER, 2024)
In this study, we explored late-time cosmology within an extended class of theories based on f(Q, L-m) gravity. This theory generalizes f(Q) gravity by incorporating a non-minimal coupling between the non-metricity Q and the matter Lagrangian L-m, analogous to the f(Q,T) theory. The coupling between Q and L-m leads to the non-conservation of the matter energy-momentum tensor. We first investigated a cosmological model defined by the functional form f(Q, L-m)=alpha Q+beta L-m(n), where alpha, beta, and n are constants. The derived Hubble parameter H(z) = H-0(1+z)(3n/2(2n-1)) indicates that n significantly influences the scaling of H(z) over cosmic history, with n > 2 suggesting accelerated expansion. We also examined the simplified case of n = 1, leading to the linear form f(Q, L-m) = alpha Q+beta L-m, consistent with a universe dominated by non-relativistic matter. Using various observational datasets, including H(z) and Pantheon, we constrained the model parameters. Our analysis showed that the f(Q, L-m) model aligns well with observational results and exhibits similar behavior to the Lambda CDM model. The results, with q(0) = -0.22 +/- 0.01 across all datasets, indicate an accelerating universe, highlighting the model's potential as an alternative to Lambda CDM.
Keywords: f(Q, L-m)gravity; Late-time cosmology; Observational constraints; TRANSITION REDSHIFT; HUBBLE CONSTANT; CONSTRAINTS; DECELERATION; UNIVERSE; PARAMETER; MODEL; F(Q; Astronomy & Astrophysics